Comparison of the Opinions of School Management and Students of the Faculty of Sports on the Use of School Spaces for Physical Activity - Ivan Čuk; Barbara Viki Šubic; Ljudmila Koprivec; Martina Zbašnik-Senegačnik (Igra Ustvarjalnosti, 2023)
Statutory and by-law regulations determine the functioning of the primary school, and within this also define the way these premises are used. Within the framework of the project Designing guidelines for the quality design of modern school architecture with the aim of supporting a comprehensive sustainable way of living and working in school, an important goal is to establish opportunities for a movement-friendly school. The goal was to check the attitude of school leaders (with many years of experience) and the future professional sports public (without many years of experience) to the use of different school facilities for the realization of supporting physical activity. Questionnaires were filled out by 21 elementary school principals and 72 students in the third year of first-level studies and the first year of second-level studies at the Ljubljana Faculty of Sports. Both groups would make significantly better use of the existing spaces for physical activity, but in comparison, managements are more in favor of the occasional use of school spaces such as classrooms, corridors and multi-purpose halls, outdoor children's and outdoor sports grounds for sports activities; the managements estimate that there are not enough toilets, shower cubicles, hand basins in their schools, both found a lack of foot basins; students notice more that students do not shower after practice; a slightly smaller proportion of management would practice athletics, gymnastics, football and handball in gyms; the proportion of managers who would dedicate corridors and a multi-purpose hall to football in the future is higher, and the proportion of those who plan athletic content on the outdoor children's playground is lower.